Using workforce analytics to improve strategy execution - Levenson, Alec (Human Resource Management, 2018)
In this article, I introduce an approach to conducting workforce analytics that is designed to improve strategy execution and organizational effectiveness through the application of systems diagnostics. What differentiates the approach are two analytic steps that precede the analyses that are typical of workforce analytics today: competitive advantage analytics and enterprise analytics. Conducting these two additional steps enables the analyst to identify the critical business issues that are the biggest problems for senior business leaders, and to determine if structural issues coming from the organization design and culture are at play. First conducting those analyses best enables traditional workforce analytics to provide insights the organization's leadership views as truly valuable.